Reducing stunting in India: what investments are needed? - Avula, Rasmi; Raykar, Neha; Menon, Purnima; Laxminarayan, Ramanan (Wiley, 2016)
India has among the highest rates of child malnutrition rates in the world, but these rates have been declining rapidly during the past decade. Between 2006 and 2014, stunting rates for children under five in India have declined from 48 to 38% (Global Nutrition Report, 2014). Despite this progress, child undernutrition rates in India are among the highest in the world, with nearly one-half of all children under 3 years of age being either underweight or stunted. India is still home to over 40 million stunted children and 17 million wasted children (Global Nutrition Report, 2014). In addition, the rates of decline have been highly variable across India's states. Some states, including Arunachal Pradesh, Mizoram and Delhi, had large rates of reduction in stunting, but overall levels of undernutrition remained high because of high baseline rates. Meanwhile, in Uttar Pradesh, Jammu and Kashmir, Manipur and Jharkhand the situation has not changed significantly (Raykar et al., 2015). Similar variability is observed in the prevalence of anaemia rates as well, which range from 38% in Goa to 78% in Bihar (IIPS & Macro International, International Institute for Population Sciences (IIPS) and Macro International, 2007).